(untitled) (Revista de Administração, 2015)
The objective of this research was to investigate the filmic language as a metaphor for communication for the analysis of the speeches in organizations. This is a qualitative research, with use of film analysis strategy. Data were collected by means of indirect and non participant observation, registered in observation protocol. It was used a strategy of discourse analysis of the personage of King George VI in the business/artistic film The king's speech; the documentary analysis of the documentary movie The king speaks – “The true story behind the film” and the content analysis of literary biography The king's speech – “as a man saved the British monarchy”. The results have reinforced that the use of film language, in this research, contributes to the understanding of the communication phenomenon in organizations. Its use creates the opportunity of simulation as from scenes that can be compared with data inserted into organizational context as metaphors, provided we are careful with the affective dimension involved in the process of filmic signification. Its utilization becomes convenient since it does not allow the choice of the film merely by the film and that there is an alignment between the movie chosen and the construct it intends to investigate.